Czy nuda w szkole może stanowić barierę w edukacji? - Iga Kazimierczyk (Problemy Wczesnej Edukacji)
Analysing the phenomenon of boredom in the context of educational barriers, I assume that the boredom is the one of the negative emotions. We experience boredom not only at school. That is why, the goal of research in pedagogy should be getting to know its specificity. Unfortunately, research work on boredom is not undertaken willingly. This has consequences: we do not know enough about the emotion of boredom and thus – we are not aware of existence of its consequences and limitations. In the article I present the results of research conducted in a group of students and teachers. The aim of the study was to understand how they see, feel and describe boredom. In the article I focus on barriers such as lack of knowledge about boredom, social learning of boredom, inhibition of conversation and communication process in the classroom, training of social isolation, feelings of fear, the threat of lower school achievements, poorer functioning and well-being of the student, equation of boredom with lack of being busy, and acceptance of boredom as a taboo.